MANAJEMEN PENDIDIKAN ISLAM SEBAGAI SENI, ILMU DAN PROFESI DI ERA SOCIETY 5.0 - Hermawansyah Hermawansyah (FiTUA: Jurnal Studi Islam, 2022)
Management of Islamic education is a collaboration between "Management" as a governing procedure, Education is placed as a container that accommodates various treasures of knowledge. In this section, a causal law or causality effect is structured which becomes disciplined and rule-abiding children because the management process is managed effectively. And the success of this causal effect is also determined by professional and consistent workers who are progressing. Responding to science, art and profession in the world of Islamic education management. First, the purpose of management as a science is to implement programs and plans according to capacity and structured in a systematic and realistic-scientific manner. Second, the purpose of management as art is to manage and regulate a system that is built on the basis of awareness and common goals. Third, the purpose of management as a profession is to realize professional and wise human resources in managing a system and being precise in decisions.